PS 02-17 IS GLYCATED HEMOGLOBIN LEVEL AND SUBCLINICAL ATHEROSCLEROSIS RELATED IN NON-DIABETIC INDIVIDUALS?. (September 2016) - Song, Yeo-Jeong; Kim, Dong-Soo; Bang, Woo-Dae; Ha, Sang Jin; Yoo, Sang-Yong; Cheong, SangSig
Abstract : Objective: To analyze the relationship between glycated hemoglobin A1 (HbA1c) levels and subclinical atherosclerosis assessed by carotid intima-media thickness (IMT), presence of carotid plaque (CP) and pulse wave velocity (PWV) in patients without diabetes. Design and Method: From January 2011 through December 2012, carotid IMT and CP presence were evaluated in 214 non-diabetes patients (118 male, 96 female) with measurement of HbA1c, ankle-brachial index (ABI), brachial/femoral and heart to femoral PWV. HbA1c level was categorized into 3 groups (< 5.5%, 5.5% to 5.9%, and 6.0% to 6.4%). Results: Baseline characteristics were similar between three groups except age. There were no significant linear trends between groups either in PWV and carotid IMT measurement; however, the presence of CP showed significant linear trend ( P for trend = 0.004). Odd ratios (ORs) of univariate model for presence of CP was 2.36 and 3.6 in the middle (5.5⩽ HbA1c   <   6.0) and highest HbA1c (6.0 ⩽ HbA1c   <  6.5) group compared with the lowest group (HbA1c   <   5.5%) (p = 0.018 and p = 0.009, respectively). Sub-analysis of 115 non-diabetic patients (57 male, 58 female) with hypertension showed poor agreement in linear increase of carotid IMT, PWV measurements and plaque presence according to the elevation of HbA1c level which the result might have been influenced by other factors. Conclusions: Carotid IMT and PWV in non-diabetic individuals had poor correlation with HbA1c level; however, there was a significant linear relation between three groups in presence of CP. Figure. No caption available.